Diagnostic performance of image technique based transurethral resection for non-muscle invasive bladder cancer: systematic review and diagnostic meta-analysis - Jian Huang; Hao Liu; Yue Zhao; Changhao Chen; Hao Huang; Richard Sylvester; Tianxin Lin (BMJ Open)
Objective To explore the diagnostic performance of image technique based transurethral resection for bladder cancer, with white light-guided cystoscopy (WLC) as the reference standard.Design Systematic review and meta-analysis.Data sources PubMed/MEDLINE, Web of Science, the Cochrane Library, Central Register of Controlled Trials and Embase from inception to 31 March 2018.Methods Included studies reported the diagnostic performance of photodynamic diagnosis (PDD) with 5-aminolevulinic acid (5-ALA), PDD with hexaminolevulinic acid (HAL) or narrow band imaging (NBI), with WLC as the reference standard at the patient or lesion level. The studies’ risk of bias (RoB) was assessed using Quality Assessment of Diagnostic Studies-2. Data were pooled using a random effect diagnostic meta-analysis, and subgroup analyses were performed.Results Twenty-six studies comprising a total of 3979 patients were included in this diagnostic meta-analysis. Pooled sensitivity (SSY), specificity (SPY), diagnostic OR (DOR) and area under the receiver operating characteristic curve (AUROC) values were calculated per group for NBI, HAL and 5-ALA at the lesion or patient level. NBI showed significant diagnostic superiority compared with WLC at the lesion level (SSY 0.94, 95% CI 0.82 to 0.98; SPY 0.79, 95% CI 0.73 to 0.85; DOR 40.09, 95% CI 20.08 to 80.01; AUROC 0.88, 95% CI 0.85 to 0.91). NBI presented the highest DOR (358.71, 95% CI 44.50 to 2891.71) in the patient level. Subgroup analyses were performed on studies with low to moderate RoB and at least 100 patients at the lesion level. These results were consistent with those of the overall analysis.Conclusions Pooled data indicated that image technique based transurethral resection (NBI, HAL and 5-ALA) showed diagnostic superiority compared with WLC. Moreover, NBI is potentially the most promising diagnostic intervention, showing the best diagnostic performance outcomes. Further prognostic outcomes of novel imaging technologies compared with those WLC should be explored in addition to current diagnostic performance analysis.